1989
DOI: 10.1104/pp.90.4.1636
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Effects of Divalent Cations on the Coupled Activities of the H+-ATPase in Tonoplast Vesicles

Abstract: The substrate requirement of the H*-ATPase in purified com root tonoplast vesicles was investigated. The coupled activities, ATP hydrolysis and proton pumping, were simultaneously supported only by Mg2' or Mn2+. The presence of Ca2+ or Ba2+ did not significantiy affect the coupled activities. The addition of Cd2', Co2+, Cu2+, and Zn2' inhibited both the hydrolysis of Mg-ATP and the proton transport. However, the inhibition of proton pumping was more pronounced. Based on equilibrium analysis, both ATP-complexed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The results described in this study provide further evidence to support our previous hypothesis (27,29,30) tional groups essential for the differential inhibition of proton pumping. As an example, the ineffectiveness of cyclic derivatives III illustrates that the presence of multiple H-bonding groups probably form the basis for the inhibitory nature of derivatives II.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results described in this study provide further evidence to support our previous hypothesis (27,29,30) tional groups essential for the differential inhibition of proton pumping. As an example, the ineffectiveness of cyclic derivatives III illustrates that the presence of multiple H-bonding groups probably form the basis for the inhibitory nature of derivatives II.…”
Section: Discussionsupporting
confidence: 89%
“…The purity of the derivatives was established by HPTLC2 and IR movement, then Equation 5 assumes the form of F, = F, -AF*exp(-k,t) (6) As described in our previous report (30), an identical mathematical expression as Equation 6, was obtained by direct curve fitting (1 1). We have demonstrated previously (27,29) that under experimental conditions, ATP hydrolysis remained constant during the buildup of the proton gradient in corn root tonoplast vesicles.…”
Section: Proton Pumpingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Inesi and de Meis (9) have proposed that the Ca transport and ATP hydrolysis by the sarcoplasmic reticulum pump are indirectly coupled. An indirect coupling mechanism has been proposed for the maize root tonoplast H+-ATPase to explain the increased sensitivity of proton transport to nitrate (18), divalent cations (19), and temperature (17) relative to ATP hydrolysis. Therefore, the reaction mechanism of the plasma membrane-type ATPases may be modeled better by an indirect coupling mechanism rather than a direct mechanism, in which transport and ATP hydrolysis share at least one step (12) as exemplified by the PostAlber cycle of the Na, K, ATPase (11) and the coupling between nucleotide displacement and reorientation of the Ca binding sites with the sacroplasmic reticulum ATPase (1).…”
Section: Discussionmentioning
confidence: 99%
“…Such root-induced changes of rhizosphere pH play a major role in the bioavailability of many pH dependent nutrients, but also potentially toxic metals and a range of trace metals (Hinsinger et al 2006). Tu et al (1989) observed that Cd has an inhibitory action on H + excretion, and proton pump activity decreased by 60% when plants grew in the solution with 50µM Cd. Proton pump is important for providing energy in the uptake and movement of ions through plasma membrane.…”
Section: Rhizosphere Ph and CD Bioavailability And Toxicitymentioning
confidence: 99%